Transcript-Based Lesson Analysis: The Analysis of Classroom Communication in Chemistry Implementing Case-Based and Project-Based Learning - Atiek Winarti; Rilia Iriani; Paul Kwame Butakor; Ruli Meiliawati; Syarpin Syarpin (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
Previous research studies found that Case-Based Method (CBM) and Project-Based Learning (PBL) models increase student motivation, critical thinking, and problem-solving. However, so far, the success of implementing these models has mostly been based on learning outcomes. Not many research studies have been carried out to reveal the effectiveness of these models by analyzing the learning process. This research is a qualitative descriptive study that aims to analyze classroom communication on solving problems in Chemistry lessons implementing the CBM and PBL models using Transcript Based Lesson Analysis (TBLA). TBLA is an analysis method based on communication occurring in the classroom. In this research, TBLA analyzes the classroom communication on solving problems in the Wood Chemistry course at the Department of Chemistry Education, Lambung Mangkurat University, Indonesia. A total of 26 students were involved. The classroom communication was recorded by camcorders and the data were transformed into transcripts. The data was processed using Excel to produce a TBLA graph. The results show that (1) the ratio of lecturer and student communication intensity using the CBM model in the classroom is 1:3, and the PBL model is 1:1. (2) The CBM model provides a good environment for the development of student HOTS through in-depth multi-directional communication patterns in the problem-solving process. (3) PBL builds better collaboration between students compared to the CBM model. This research implies that the quality of classroom communication can be improved by integrating the HOTS questions and independent group work as implemented in the CBM and PBL models.